Analysis of Organic Lettuce Supply Chain Institutions - Sajali, Chusnatul Ulaela; Setiawan, Budi; Koestiono, Djoko (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2018)
Supply chains are formed due to the need of farmers, wholesalers, retailers, supermarkets, and consumers. With a large number of agents in the organic lettuce production starting from the farmers up to supermarkets, it turns out that supply chain management has not proceeded well. Each agent has still no-good cooperation and relationship because they only work and focus on their own goals. Information desired by consumers only reaches the retailers, not up to the farmers as suppliers. This research was aimed to identify the structure of organic lettuce supply chain flow, to analyze the performance of organic lettuce supply chain management, and to formulate alternative solutions for the management performance improvement in the organic lettuce supply chain. The results showed that the agents of the supply chain in the flow of information have not flowed perfectly and completely. Improved and better supply chain management performance is highly required at wholesalers and retailers.